2010
DOI: 10.1158/0008-5472.can-10-0600
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ Markedly Cooperates with Intratumoral Dendritic Cell Vaccine in Dog Tumor Models

Abstract: Dendritic cell (DC)-based immunotherapy can trigger effective immune responses against cancer in human patients. Although accompanied by little toxicity, further improvements are needed to optimize immune responses for fully satisfactory clinical outcomes. IFNγ, a potent inducer of T helper type 1 immune responses, is considered an important tool to realize improvements. In this study, we sought to clarify the effect of IFNγ on the maturation and activation of DCs and the clinical outcome of DC-based cancer th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Pro-inflammatory cytokine TNF-α can augment inflammatory responses by acting on many immune and non-immune cells as well as by stimulating the secretion of other pro-inflammatory cytokines [24,25]. Besides, IFN-γ can promote both the innate and adaptive immune responses against tumor cells and a variety of infectious agents [26,27]; it is also critical in the development of inflammatory diseases [27]. Therefore, by attenuating the expression of these critical cytokines, CucE may suppress adaptive immune responses mediated by T cells, thereby dampening ongoing inflammatory responses and contributing to its therapeutic activity in controlling inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokine TNF-α can augment inflammatory responses by acting on many immune and non-immune cells as well as by stimulating the secretion of other pro-inflammatory cytokines [24,25]. Besides, IFN-γ can promote both the innate and adaptive immune responses against tumor cells and a variety of infectious agents [26,27]; it is also critical in the development of inflammatory diseases [27]. Therefore, by attenuating the expression of these critical cytokines, CucE may suppress adaptive immune responses mediated by T cells, thereby dampening ongoing inflammatory responses and contributing to its therapeutic activity in controlling inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…I.t. injection of immature DCs and IFNgamma into malignant tumors in dogs produced anti-tumor immunity including four complete responses and two partial responses out of seven treated dogs [99]. In B16 melanoma, i.t.…”
Section: It Immunotherapy With Activated Immune Cellsmentioning
confidence: 93%
“…As ex vivo-generated, antigen-loaded DCs have poor anti-tumor effects [40][41][42], new alternatives such as IFN-␥ DCs or IL-15 DCs are emerging and have better efficiency in inducing antigen-specific CTL priming [27][28][29]. Nicotine, known as a chemical compound with advantages of chemical stability and economic, caught much attention for its stimulation to enhance DCs' ability of mediating T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that IFN-␥, IL-15 and IL-18 have bioactivities to augment DCs' functions [27][28][29]. We compared the stimulation efficiency of nicotine with other cytokines, as potential clinical implication of nicotine stimulated DCs was considered.…”
Section: Ctl Induced By Nicotine-treated Dcs In Vivo Had Specific Cytmentioning
confidence: 99%
See 1 more Smart Citation